ASSESSMENT OF THE IMPACTS OF BUSINESS ENVIRONMENT ON THE DEVELOPMENT OF VIETNAMESE SMEs: EVIDENCE FROM THE ENTERPRISE SURVEY - Nguyễn Quốc Định (Tạp chí Khoa học Đại học Đà Lạt)
Many studies have shown that a firm’s growth depends considerably on business environment. In this study, the employment growth of SMEs in Vietnam is investigated with respect to its crucial role in the entire economy. The results of the regression analysis of fixed-effect model show that informal payment, low institution quality, and tax inspections are hindering the employment growth of SMEs in Vietnam while expanding the access to finance can help SMEs develop. Based on the rigorous analysis, some possible recommendations are provided: (i) Expanding application of information technology in tax administration; (ii) Reducing complicated sub-licenses and administrative procedures; (iii) Reducing business risks of firms by establishing a specific business strategy and long-term vision; and (iv) Decreasing the chances of corruption by simplifying and rationalizing the regulatory loopholes as well as increasing transparency in making laws/policies.